Strategi Visual Punden Berundak Situs Gunung Padang dalam Genre Fotografi Landscape sebagai Pesan Budaya - Winny Gunarti Widya Wardani; Wulandari Wulandari; Syahid Syahid (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Gunung Padang Site in Cianjur is a cone-shaped hill area filled with relics of the Megalithic era in the form of stone objects. Punden terraces – a place for the worship of ancestral spirits – has become a hallmark and an important cultural heritage as a part of the distinctive characteristics of the indigenous culture in Nusantara. This study aims to communicate the cultural message of the punden terraces through the visual strategy of photography with the landscape genre, the art of photography that explores the beauty of nature and sharpens the landscape. Quantitatively, this study conducted a survey to find out the attraction of the photo objects. The result showed that the majority of respondents considered the scenery on the Gunung Padang Site to be more interesting than the stone objects and the daily life of surrounding communities. Whereas qualitatively, this study discusses the elements of visual strategy using the theory of photography with visual communication semiotic approach, especially in terms of the shot sizes and the framing of visual space. Punden terraces' photographs in landscape photography are able to communicate cultural messages about human activity in the past. This, in turn, will contribute to enriching scientific references of visual communication design